Brief Clinical Screening for Academic Underachievement in New Onset Childhood Epilepsy: Utility and Longitudinal Results - Almane, Dace (Epilepsy Behav, 2015)
OBJECTIVE: To determine the lifetime rate and distribution of supportive academic and educational services provided to children with new/recent onset epilepsy and typically-developing controls, the relationship of this history to objective academic test performance, and the course of performance over serial evaluations (baseline, 2 and 5 years later). METHODS: Research participants were 91 children aged 8-18 at study entry, including 50 youth with recent-onset epilepsy (28 Focal [FE] and 22 Generalized [GE] epilepsy) and healthy first-degree cousin controls (n=41). Epilepsy sample included children with uncomplicated epilepsy, normal imaging and development. Lifetime history of a diversity of supportive educational services was determined via structured interview with parents at the baseline study visit. Associations were examined between these support services and participants' academic performance in reading, spelling, and arithmetic (Wide Range Achievement Test Rev. 3 [WRAT3][1]) during three serial study visits including baseline, 2 and 5-years later. RESULTS: Children with epilepsy had a higher lifetime rate of provision of diverse academic supportive services compared to controls at the baseline visit (52% vs. 18%). These services antedated epilepsy diagnosis in the majority (80.8%) of the children with epilepsy. Among children with epilepsy, children who presented with academic services had significantly lower WRAT3 reading, spelling, and arithmetic performance at baseline, 2 and 5-year follow-up. CONCLUSION: A brief structured clinical interview conducted with parents identifies children with epilepsy who are at academic risk at the time of diagnosis with that risk persisting up to 5-years later.